Impacts of train-induced dynamic loads on goaf foundation of Qinshui coalfield - Wang, Hui; Zhou, Jing; Cheng, Jianhua; Dun, Zhilin; Dun, Zhiyuan (Frontiers in Earth Science, 2023)
For the high-speed railway built in the goaf sites, if the influence depth of the additional loads reaches the collapse fault zone of the goaf foundation, the overburden rock mass above the mined area will move again, causing the surface to deform again, which seriously threatens the construction, operation, and maintenance of the high-speed railway lines. Therefore, in order to improve the safety and stability of operation of high-speed railway in goaf sites, it is essential to determine the activation deformation of the goaf foundation. In this paper, based on the additional stress method, the newly added embankment materials are taken as uniformly distributed strip static loads, and the high-speed railway in operation is regarded as the fluctuation-concentrated dynamic loads. The 1/4 vehicle vibration model with two degrees of freedom is introduced, and the influence depth of the additional loads of the goaf foundation is calculated. The criterion of activation is proposed based on the relationship between the influence depth of additional loads and the height of the collapse zone and fault zone. Conclusions drawn are as follows: i) the activation judgment criterion for the goaf foundation under the influence of high-speed railway vibration loads is recommended; ii) case study shows that the rail surface vibration model applicable to quantify the influence depth of high-speed railway mentioned previously mined-out regions; iii) the influence of rail surface irregularity on influence depth cannot be ignored; iv) the research conclusion can provide reference for site selection of high-speed railway and embankment deformation analysis.